Hidden from the outside world : Narratives of the sex trafficking survivors in public media - Lammervo, Elina (My University, 2023)
Sex trafficking is an universally widespread phenomenon that exist in various forms of sex work and sexual exploitation. Different societal conflicts and wars typically proliferate sex trafficking as well as its coverage in media. Nevertheless, the phenomenon is constantly and globally present whether or not it would be a topic in public discussion. Sex workers have historically been featured as an ordinary part of society, since prostitution is termed the ‘oldest profession on earth’. Globally, over the past few decades, the increased use of information and communication technologies has led to the use of pornography on an endemic scale. However, whilst sexual work is somewhat normalised and widely publicised, there is still a lack of realisation that many sex workers may be victims of human trafficking. Sex trafficking victims are typically perceived as prostitutes, or in an international context, illegal immigrants. This causes their victim-status to remain unidentified in which case they are often hindered from receiving the help they need. Moreover, prostitution is a highly stigmatised occupation. Victims of sex trafficking therefore typically are stigmatised as prostitutes even though they have entered in the sex trade against their will. This thesis examines narratives of sex trafficking survivors. The stories are collected from different media where the survivors have given personal accounts of their own experiences. This study combines these stories into a uniform narrative that follows their experiences from childhood to the point of the documentation of their narratives. The research explores how the survivors describe their identities along the timeline of their narratives and reports other people’s perceptions of them as they emerge in their stories. The thesis analyses the stereotypical presumptions of sex trafficking that are based on the survivors’ descriptions as well as on the research about the subject. The concepts of deviance and stigma (Goffman 1963) are used as theoretical concepts in the analysis. The findings show that the survivors suffer from various forms of trauma that exist in their everyday life even years after escaping from trafficking. Survivors demonstrate various ways of managing the stigma of sex trafficking life imprinted on them. Childhood experiences, such as sexual and mental abuse, had impact on how the survivors explained the causality of being drawn into sex trafficking. The narratives raise issues of familial trafficking and the intersectional problems of being a homosexual, poor and homeless. The stories reveal the importance of early intervention of child abuse, support of underaged homosexuals and the identification of sex trafficking victims.
Keywords: sex trafficking, human trafficking, sexual exploitation, sexual abuse, sexual violence, trauma, sex work, stigma, deviance